Intelligent Algorithm Deep Learning Reinforcement Learning Module Integrated into the Navigation System to Enhance the Ability of Navigation to Accurately Serve Users - Li Jinhao (MATEC Web of Conferences)
In the increasingly competitive automotive industry, the in - car navigation system, a crucial aspect of the user experience, demands greater personalization and intelligence. This research aims to design a navigation system that better caters to users’ needs, thereby enhancing the driving experience and user satisfaction. The research employs a combination of user research, data analysis, and prototype design methods. Initially, the navigation requirements of different user groups are gathered through questionnaire surveys and user interviews. Subsequently, machine - learning algorithms are utilized to analyze user behavior data, identifying personalized demand patterns. Based on these analysis results, an intelligent navigation system prototype is designed and developed, featuring real - time road condition optimization, personalized route recommendation, and voice interaction functions. Experimental results demonstrate that the system significantly improves navigation efficiency and user satisfaction, particularly in complex road conditions, outperforming traditional navigation systems. The innovation of this research lies in integrating user behavior analysis with intelligent algorithms to achieve personalized customization of the navigation system, addressing the inadequacy of traditional navigation systems in meeting diverse user needs. The research findings offer new insights and technical support for the future design of in - car navigation systems.